Assessment of unsaturated behavior of Gorgan loessial soil under anisotropic triaxial compression in medium suctions range - S. Mohsen Haeri; B. Sadollahzadeh; s. soleymani borujerdi (مهندسی عمران شریف)
Collapsible soils, such as loess, are classified as problematic soils and are usually stable in unsaturated conditions in nature. However, when they are exposed to a moisture increase, especially under an applied load, they undergo a sudden decrease in volume or collapse. Various aspects of the behavior of unsaturated collapsible soils including volume change, soil-water retention, and shear strength have been extensively investigated so far. However, few studies have been carried out on the effect of initial shear stress on the hydromechanical behavior of unsaturated collapsible soils. This study aims to investigate the effect of initial shear stress on the hydromechanical behavior of Gorgan loessial soil under isotropic and anisotropic triaxial compression in the medium suctions including 300 and 400 kPa using a fully automated unsaturated triaxial device. In this study, a set of stress-controlled triaxial tests were performed on reconstituted specimens of Gorgan loessial soil implementing a “suction decrease under constant mean net stress” hydromechanical stress path. The tests were conducted in medium-range suctions under different initial shear stresses. Strain-controlled triaxial shear tests were also conducted at the end of isotropic and anisotropic compression, to evaluate the shear behavior of the tested specimens. Results taken from the wetting stage indicate that the volume reduction of the specimens increases with an increase in initial shear stress under constant mean net stress. The results obtained from shear tests on specimens with constant matric suction and mean net stress in the wetting stage show that the greater the initial shear stress, the lower the shear strength of the specimen. Also, according to the independent stress variables approach, the shear resistance parameters including c´, ϕ´, and ϕb have been obtained at 4.7 kPa, 32.9°, and 13.6°, respectively. In addition, regression lines through the steady-state data points, used to define the CSL of the reconstituted specimens, had an M-value of 1.19.